RADIOGRAPH EVALUATION OF ROOT CANAL TREATMENT USING PERIAPICAL INDEX, STRINDBERG’S CRITERIA AND MOLVEN’S CRITERIA - Sofiani, Erma; Ramadanti, Annisa (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Periapical disease can be treated by endodontic treatment. One way to evaluate the success of the root canal treatment is operating the treatment radiographically used Periapical Index, Strindberg’s Criteria dan Molven’s Criteria. Along with the development of technology, one of the tools that can be used is Computed Radiography. This tool is used to detect abnormalities and periapical healing process. Evaluating the success of root canal treatment using Computed Radiography with Periapical Index, Strindberg's Criteria and Molven's Criteria. Methods. The research sample is computed radiography data at Academic Dental Hospital within a total of 48 samples of single root canal teeth. The observation was observed by two observers through the google form link, before and after root canal treatment according to the criteria. The final results of this research were analyzed using Kappa Test, Kruskal Wallis Non-Parametric Test and Mann Whitney Post Hoc Test. Results & Analysis. The kappa or agreement value of the assessment was higher on the Strindberg's Criteria with a fairly high interpretation compared to the Periapical Index and Molven's Criteria, both of which only scored moderately. There are different assessments when using different types of assessment on the Periapical Index and Strindberg's Criteria. Discussion. There are different assessments when using different types of assessment on the Periapical Index and Strindberg's Criteria. Agreement value of the assessment was higher on the Strindberg's Criteria with a fairly high interpretation.